Clinical Profile of Thyroid Disorders – A retrospective study at BPKIHS - Agrawal, Anuskha; Rani, Nidhi; Maskey, Robin (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Background: The thyroid gland produces two key metabolic hormones which regulate metabolic rate, growth and development. They play vital roles in digestion, heart and muscle function, brain development and maintenance of bones. People suffering from thyroid disorders may have autoimmune disease, ranging from primary hypothyroidism, Hashimoto’s thyroiditis, to hyperthyroidism caused by Graves’ disease.Objectives: To study clinical profile of thyroid disorders in endocrinology clinic of BPKIHS, Nepal.Methods: This is a hospital based retrospective study of past five years (2012 – 2017) done in department of internal medicine at B.P. Koirala Institute of Health Sciences, in which thyroid disorder patient records from the endocrinology clinic will be compiled together will be analyzed after classifying them according to the guidelines of the American Thyroid Association (ATA). Results: Among 584 thyroid disorder cases that were sampled, higher prevalence of thyroid disorders was seen in females, and the Male: Female ratio was 1:4.13. Most common type of thyroid disorder was Hypothyroidism (29.6%) followed by Subclinical hypothyroidism (28.3%).Conclusions: Thyroid disorders are more common in females than males and hypothyroidism being commonest thyroid disorder in our setup. Subclinical hypothyroidism is second commonest followed by hyperthyroidism. In Subclinical hypothyroidism Anti TPO antibody is most commonly found to be positive.